Tillage type and sentinel insect species affect the relative prevalence of the entomopathogenic fungus, Metarhizium robertsii, in soil. - Shea A W Tillotson; Christina A Voortman; John M Wallace; Mary E Barbercheck (PLoS ONE)
Because the use of synthetic agrochemicals is generally not allowed in organic crop production systems, growers rely on natural substances and processes, such as microbial control, to suppress insect pests. Reduced tillage practices are associated with beneficial soil organisms, such as entomopathogenic fungi, that can contribute to the natural control of insect pests. The impacts of management, such as tillage, in a cropping system can affect soil biota in the current season and can also persist over time as legacy effects. We investigated the in-season and legacy effects of soil management in four, three-year organic feed grain and forage production systems that varied in number and intensity of soil disturbances on the relative prevalence of the entomopathogenic fungus, Metarhizium robertsii. Employing sentinel bait assays with Tenebrio molitor and Galleria mellonella, we found that relative prevalence, measured as infection rate of sentinel insects, was lowest in systems utilizing a shallow high-speed disk (G. mellonella: 14%; T. molitor: 23%) in the current and previous seasons compared to systems that included inversion and non-inversion tillage (G. mellonella: 22%; T. molitor: 34%) or no-till planting (G. mellonella: 21%; T. molitor: 30%,). There was no difference in prevalence in systems that included the use of a high-speed disk compared to a perennial hay crop (G. mellonella: 16%; T. molitor: 28%). There were no negative legacy effects of inversion tillage on the prevalence of M. robertsii in subsequent crops. Sentinel assays with G. mellonella (19%) produced overall lower estimates of relative prevalence of M. robertsii than T. molitor (29%) but the association of relative prevalence with environmental variables was greater in assays with G. mellonella. We suggest that the use of occasional inversion tillage is not damaging to populations of M. robertsii in soil and that surveys using assays with multiple sentinel insect species will improve our ability to understand the effects of agricultural practices on entomopathogenic fungi.